From Counsel to the Aisle: The Practice of Markobar within the Framework of ‘Urf and the Ideal Concept of Marriage in Mandailing - Musthafa, Halum; Azwar, Zainal; Mardiyah, Azizah; Hasibuan, Marzuki Hafiz Alhamdani (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study aims to examine the markobar tradition in walimatul ‘ursy (wedding banquet) ceremonies within the Mandailing community, as well as to analyze this practice from the perspective of Islamic law (?urf) and its contribution to the formation of a sakinah, mawaddah, wa rahmah (tranquil, loving, and compassionate) family. The markobar tradition is an oral cultural heritage rich in local, religious, and moral values passed down through generations. The main focus of this research is to understand how markobar is practiced, to analyze the cultural and religious values it contains, and to explore the role this tradition plays in supporting the formation of a harmonious and loving Islamic family in accordance with Islamic law. The research employs a descriptive qualitative approach, with data collected through in-depth interviews and documentation of Mandailing customary literature and Islamic legal references. The data were analyzed using a content analysis approach to identify key themes related to the implementation of markobar and the foundations of ?urf that support it. The findings show that markobar falls under the category of ?urf ?a???, which refers to community customs that do not contradict Islamic principles. This tradition plays a significant role in imparting marital advice and strengthening the value of togetherness within the household, thereby contributing to the formation of a samawa (sakinah, mawaddah, wa rahmah) family. The study recommends reinforcing the preservation of the markobar tradition as part of the harmonization between local culture and Islamic law and encourages greater involvement of the younger generation in sustaining traditions that support the development of sustainable Islamic families. Abstract: Penelitian ini bertujuan untuk mengkaji tradisi markobar dalam acara walimatul ‘ursy pada komunitas Mandailing, serta menelaah praktik tersebut dari perspektif hukum Islam (‘urf) dan kontribusinya dalam pembentukan keluarga sakinah mawaddah warahmah. Tradisi markobar merupakan warisan budaya lisan yang sarat dengan nilai-nilai lokal, religius, dan moral yang diwariskan secara turun-temurun. Fokus utama penelitian ini adalah memahami bagaimana markobar dijalankan, menelaah nilai budaya dan keagamaan yang terkandung di dalamnya, serta mengeksplorasi peran tradisi ini dalam mendukung pembentukan keluarga Islami yang harmonis dan penuh kasih sayang sesuai syariat Islam. Metode yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam serta dokumentasi terhadap literatur adat Mandailing dan referensi hukum Islam. Data dianalisis menggunakan pendekatan analisis isi untuk mengidentifikasi tema-tema utama terkait pelaksanaan markobar dan dasar-dasar ‘urf yang mendukungnya. Hasil penelitian menunjukkan bahwa markobar termasuk dalam kategori ‘urf sahih, yaitu kebiasaan masyarakat yang tidak bertentangan dengan syariat Islam. Tradisi ini memainkan peran penting dalam menanamkan nasihat pernikahan dan memperkuat nilai kebersamaan dalam rumah tangga sehingga terbentuknya keluarga samawa. Penelitian ini merekomendasikan penguatan pelestarian tradisi markobar sebagai bagian dari harmonisasi antara budaya lokal dan hukum Islam, serta mendorong keterlibatan generasi muda dalam mempertahankan tradisi yang mendukung terbentuknya keluarga Islami yang berkelanjutan